Examination of Age‐dependent effects of fetal ethanol exposure on behavior, hippocampal cell counts, and doublecortin immunoreactivity in rats. Issue 5 (3rd December 2013) - Elibol‐Can, Birsen; Dursun, Ilknur; Telkes, Ilknur; Kilic, Ertugrul; Canan, Sinan; Jakubowska‐Dogru, Ewa
ABSTRACT Ethanol is known as a potent teratogen having adverse effects on brain and behavior. However, some of the behavioral deficits caused by fetal alcohol exposure and well expressed in juveniles ameliorate with maturation may suggest some kind of functional recovery occurring during postnatal development. The aim of this study was to reexamine age‐dependent behavioral impairments in fetal‐alcohol rats and to investigate the changes in neurogenesis and gross morphology of the hippocampus during a protracted postnatal period searching for developmental deficits and/or delays that would correlate with behavioral impairments in juveniles and for potential compensatory processes responsible for their amelioration in adults. Ethanol was delivered to the pregnant dams by intragastric intubation throughout 7–21 gestation days at daily dose of 6 g/kg. Isocaloric intubation and intact control groups were included. Locomotor activity, anxiety, and spatial learning tasks were applied to juvenile and young‐adult rats from all groups. Unbiased stereological estimates of hippocampal volumes, the total number of pyramidal and granular cells, and double cortin expressing neurons were carried out for postnatal days (PDs) PD1, PD10, PD30, and PD60. Alcohol insult during second trimester equivalent caused significant deficits in the spatial learning in juvenile rats; however, its effect on hippocampal morphology was limited to a marginally lower number of granular cells in dentate gyrus (DG) on PD30. Thus, initial behavioral deficits and the following functional recovery in fetal‐alcohol subjects may be due to more subtle plastic changes within the hippocampal formation but also in other structures of the extended hippocampal circuit. Further investigation is required. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 498–513, 2014